REGISTER BAHASA TAMAN PENDIDIKAN AL QURAN DI MASJID AL MUTTAQIN KELURAHAN GOMBONG, KECAMATAN GOMBONG, KABUPATEN KEBUMEN - Musthofa Kamal As Shobari; Umi Hartati (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to describe the form, meaning, and function of the language register of the Al Quran Education Park in the Al Muttaqin mosque, Gombong Village, Gombong District, Kebumen Regency. This research is qualitative research. The method used is the method of switching with the direct element sharing technique (BUL), and using the pragmatic matching method with the differentiating comparative link technique (HBB). Informal presented methods. The results of this study are (1) The form of language registers uses the basic form and derivative form, (2) The meaning of language registers includes grammatical meaning, term meaning, and associative meaning, (3) Language register functions include emotive and conative functions.